The system design of financial literacy strengthening and taxation in creative MSMEs supports sustainable competitiveness - Pahlevi, Reza Widhar; Safitri , Adelia Rizky (Journal of Management and Business Insight, 2023)
Purpose-In order to determine whether the environment in the organization encourages creative micro, small, and medium sized enterprises to increase competitiveness through their level of financial and tax understanding, as well as encouraging organizations, this study aims to identify factors that affect the competitiveness of creative micro, small, and medium sized enterprises when viewed from that perspective. to establish a mechanism for enhancing taxation and financial literacy to boost long-term competitiveness that is then applied to creative micro, small, and medium sized enterprises. Design/Methodology/Approach-Participants in this study were from Daerah Istimewa Yogyakarta and Jawa Tengah’s creative micro, small, and medium sized enterprises. To obtain its data, this study used convenient, intentional, and snowball sampling procedures, 15 micro, small, and medium sized enterprises managers from various districts and the cities of Daerah Istimewa Yogyakarta and Jawa Tengah served as informants for this study. Combining these techniques makes it simpler to select respondents and collect data from them who have been successfully operating creative micro, small, and medium sized enterprises for more than five years. After finding the responders, the snowball sampling technique was applied. Findings-The results show that having financial knowledge may be a great asset for micro, small, and medium sized enterprises. The digital age expands market chains and boosts the creation of micro, small, and medium sized enterprises, however owing to a lack of understanding of tax legislation, not all taxpayers, including micro, small, and medium sized enterprises, can comprehend the necessary tax reporting implementation rules and processes. Additionally, micro, small, and medium sized enterprises seem to be growing as a result of strategic initiatives to raise the human resource quality and growth of micro, small, and medium sized enterprises in Daerah Istimewa Yogyakarta and Jawa Tengah. Research limitations/Implications-The limitations of a study are its flaws or shortcomings. Study limitations can exist due to constraints on research design, methodology, materials, etc., and these factors may impact the findings of your study. Originality/Value-This is your opportunity to provide readers with an analysis of the value of your results. It’s a good idea to ask colleagues whether your analysis is balanced and fair and again, it’s important not to exaggerate.